KEANEKARAGAMAN JENIS-JENIS TUMBUHAN PAKU (Pteridophyta) DI HUTAN LINDUNG JAOBAKI, DESA AJAOBAKI, KECAMATAN MOLLO UTARA, KABUPATEN TIMOR TENGAH SELATAN, PROVINSI NUSA TENGGARA TIMUR - Kolin, Robertus Berkama; Riwu Kaho, Ludji Michael; Purnama, Maria M. E. (Wana Lestari, 2022)
This research was conducted to determine the diversity of ferns (Pteridophyta). This research was conducted in the Ajaobaki Protected Forest, Ajaobaki Village, North Mollo District, South Central Timor Regency, East Nusa Tenggara Province. It was carried out for 1 month from March to April 2021. This study used a purposive sampling, survey, and transect method with data analysis using qualitative descriptive analysis and quantitative descriptive analysis. The data was processed using the Shannon Wiener (H’) diversity index formula. The results showed that environmental and ecosystem factors in the Ajaobaki protected forest area was very good for ferns silviculture. But some factors cause damage to the Ajaobaki protected forest area which can experience extinction in ferns caused by humans and livestock. There were 11 species of ferns found in the sampling plot in the Ajaobaki Protected Forest, Ajaobaki Village, consisting of 4 ferns that live on the ground (terrestrial) and 7 ferns that live on trees (epifit). The most common ferns found were Devalia Canariensis with 540 species and the least found was Drynaria Quercifolia ferns with 3 species. The level of diversity of fern species was calculated using the Shannon winner index of 1.79 (H’) for all species with moderate diversity (1≤H’≤3).